Psychosomatically Oriented Diagnostics and Therapy for Fertility Disorders. Guideline of the DGPFG (S2k-Level, AWMF Registry Number 016/003, December 2019) - Wischmann, Tewes; Borkenhagen, Ada; David, Matthias; Dorn, Almut; Dorn, Christoph; Gagsteiger, Friedrich; Goeckenjan, Maren; Ludwig, Annika; Meier-Credner, Anne; Röhrig, Michelle; Rothe-Kirchberger, Ingrid; Schick, Maren; Siegel, Stefan; Tandler-Schneider, Andreas; Thorn, Petra; Weblus, Anna Julka; Kentenich, Heribert (Geburtshilfe und Frauenheilkunde, 2021)
Aim The purpose of this official guideline published and coordinated by the German Society for Psychosomatic Gynecology and Obstetrics [Deutsche Gesellschaft für Psychosomatische Frauenheilkunde und Geburtshilfe (DGPFG)] is to provide a consensus-based overview of psychosomatically oriented diagnostic procedures and treatments for fertility disorders by evaluating the relevant literature.Method This S2k guideline was developed using a structured consensus process which included representative members of various professions; the guideline was commissioned by the DGPFG and is based on the 2014 version of the guideline.Recommendations The guideline provides recommendations on psychosomatically oriented diagnostic procedures and treatments for fertility disorders.Ziel Das Ziel dieser offiziellen Leitlinie, die von der Deutschen Gesellschaft für Psychosomatische Frauenheilkunde und Geburtshilfe (DGPFG) publiziert und koordiniert wurde, ist es, durch die Evaluation der relevanten Literatur einen konsensbasierten Überblick über die psychosomatisch orientierte Diagnostik und Therapie bei Fertilitätsstörungen zu geben.Methoden Diese S2k-Leitlinie wurde durch einen strukturierten Konsens von repräsentativen Mitgliedern verschiedener Professionen im Auftrag der DGPFG entwickelt, aufbauend auf der Leitlinienversion von 2014.Empfehlungen Es werden Empfehlungen zur psychosomatisch orientierten Diagnostik und Therapie bei Fertilitätsstörungen gegeben.
Keywords: psychosomatics; fertility disorders; guideline; reproductive medicine